Evaluating Knowledge And Awareness Of SGLT-2 Inhibitors’ Use, Efficacy, Side Effects, And Cardiovascular And Renal Impacts Among Primary Healthcare Physicians In Makkah, Saudi Arabia (The Review of Diabetic Studies, 2025)
Background: Sodium-glucose cotransporter-2 (SGLT-2) inhibitors are a class of antihyperglycemic medications primarily used for the treatment of T2DM. They have been associated with cardiovascular and renal protective effects, making them beneficial for patients with T2DM and high cardiovascular risk.Objectives: to assess the knowledge of primary healthcare physicians regarding the use, efficacy, side effects, and cardiovascular and renal impacts of Sodium-glucose cotransporter-2 (SGLT-2) inhibitors among T2DM patients.Subjects and methods: An analytical cross-sectional study was conducted on a non-probability convenience sample of primary healthcare physicians in Makkah, Saudi Arabia. Data were collected through an electronic self-administered questionnaire composed of two main parts; demographic information of the participants and multiple-choice questions to assess the level of knowledge and awareness about SGLT-2 inhibitors.Results: A total of 249 physicians participated in the study. Their age ranges between 25 and 47 years with an arithmetic mean of 32.2 and standard deviation of 4.4 years. More than half (56.6%) of them were males. history of ever prescribing SGLT-2 inhibitor medications for a diabetic patient was reported by most of the physicians (89.2%). Overall, good level of knowledge was observed among 38.6% of the physicians whereas poor level was observed among 15.7% of them. Males (p=0.002), older physicians (p=0.050), Saudis (p=0.026), those with experience of 6-10 years (0.046), physicians with lower income (p=0.001), consultants (p